Analisis Mitigasi Risiko Kesehatan Dan Keselamatan Kerja (K3) Pada Produksi Batu Bata Menggunakan Metode Job Safety Analysis (JSA) Dan House Of Risk (HOR) (Studi Kasus: UD. Sejati) - Ulfaturrahmi; Fadhilah, Fitri; Firdaus, Aqfi Nur (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2025)
UD. Sejati is a small business in Nijang Hamlet, Uter Iwes District, Sumbawa Besar, West Nusa Tenggara, which produces 500-1000 red bricks per day. This study aims to analyze the mitigation of occupational health and safety (K3) risks so that work accidents in the production process can be minimized. The study uses two main methods: Job Safety Analysis (JSA) to identify hazards in the work environment and their preventive measures. House of Risk (HOR) focuses on prevention with two stages. HOR 1 assesses potential hazards using (ARP) to determine priority risk agents. HOR 2 designs mitigation for these priority risks. The results of the study with JSA found 16 potential hazards from 15 work activities, such as eye irritation due to rice husk dust, respiratory problems, slipping, and exposure to sparks. Meanwhile, HOR 1 identified 7 priority risks (A15, A13, A5, A14, A8, A12, A7) that require further handling. In HOR 2, 13 mitigation strategies were obtained from 7 main risk agents, with the strategy priority based on the highest ETDk value, namely PA2 at 1283.25. This approach ensures effective and efficient mitigation in reducing OHS risks at UD. Sejati.